Serodiagnosis of Human Granulocytic Ehrlichiosis by Using Novel Combinations of Immunoreactive Recombinant Proteins - Lodes, Michael J. (American Society for Microbiology, 2001)
A panel of seven recombinant antigens, derived from Ehrlichia phagocytophila (the agent of human granulocytic ehrlichiosis), was evaluated by class-specific enzyme-linked immunosorbent assays (ELISAs) for utility in the diagnosis of the infection. Fourteen genomic fragments, obtained by serologic expression screening, contained open reading frames (ORFs) encoding 16 immunodominant antigens. Eleven of these antigens were members of the major surface protein (MSP) multigene family. Alignment of their predicted protein sequences revealed a pattern of conserved sequences, which contained short direct repeats, flanking a variable region. In addition, two genomic clones contained two and three MSP ORFs, respectively, indicating that these genes are clustered in tandem copies. The implications for this pattern of both genomic and protein arrangements in antigenic variations of MSPs and in their utilities in a diagnostic assay are discussed. In addition to two MSP recombinant antigens (rHGE-1 and -3) and a fusion protein of these antigens (rErf-1), five further recombinants were evaluated by ELISA. Two of these antigens (rHGE-14 and -15) were novel, while a third (rHGE-2), with no known function, has been described. The final two recombinant antigens (rHGE-9 and -17) represent overlapping segments of the ankyrin gene (ank). The addition of rHGE-9 ELISA data resulted in the detection of 78% (21 of 27) of acute-phase sera. When serologic data for all recombinants are combined, 96.2% (26 of 27) of convalescent-phase patient serum samples and 85.2% (23 of 27) of acute-phase patient serum samples are detected, indicating the potential of these antigens for use in the development of a rapid serologic assay for the detection of E. phagocytophila infection.